(untitled) (Journal of actual problems of jurisprudence, 2021)
In the article we examined some issues of the influence of historical and political factors on the formation and development of legal consciousness in the Republic of Kazakhstan, and also to identify the place of law in the system of value orientations of citizens of the Republic of Kazakhstan, we carried out practical research. Legal awareness is not a phenomenon acquired from birth, it develops for a long time and gradually. Legal consciousness is formed as a result of the interaction of the individual in society and the understanding of the received information. Legal consciousness is formed under the influence of various circumstances, current events, specific living conditions and various processes that influence the life of a society. In legal science, it is customary to consider the factors influencing the legal consciousness in the following two groups: 1. External (the activities of subjects – creators of legal consciousness). 2. Internal (individual personality characteristics). It should be noted that the process of forming legal consciousness is impossible without the socialization of the individual, since legal consciousness can only be formed if there is an individual in the social environment and the formation of relations between him and society. A.V. Mudryak justifies the need to consider the factors of socialization as special circumstances or conditions that influence this process. He identifies three groups of such factors: Macrofactors (world, country, state, society) that influence very large groups of people in certain countries, the influence is mediated by two other groups of factors. Mesofactors, conditions of socialization of large groups of people allocated: on a national basis; according to the place and type of settlement in which they live; by belonging to the audience of various mass communication networks. Mesofactors influence a person’s legal consciousness both directly and indirectly through the factors of the third group. Microfactors. These include circumstances directly affecting specific people – the family, peer groups, the microsocium, organizations in which social education is carried out – educational, professional, social, religious organizations. (Mudryak, 2000) Key words: rule of law, law, personality, sense of justice, legal culture, socialization.